2008
DOI: 10.1088/0022-3727/41/7/074029
|View full text |Cite
|
Sign up to set email alerts
|

Indentation and scratching mechanisms of a ZrCuAlNi bulk metallic glass

Abstract: Indentation and scratching tests are carried out on a ZrCuAlNi bulk metallic glass. The bonded interface technique is used to characterize the plasticity mechanisms underneath the indentation. Finite-element analyses are conducted with a Drucker-Prager behaviour law to challenge the indentation experimental data. The relevance of the bonded interface technique, in terms of quantitative evaluation, is discussed. It is also reported that the angle value, for which radial bands intersect at the surface or underne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Further loading leads to the localization of the deformation within the shear band (or in an array of parallel bands) without any strain hardening. There is a wide body of experimental evidence showing that the yield criterion for shear band formation in metallic [13][14][15][16] and ceramic glasses [17,18] as well as in polymers [19][20][21][22] depends on the hydrostatic stress and that the yield surface of these materials is adequately represented by either the Mohr-Coulomb or the Drucker-Prager yield criterion. Mathematically, the yield surface (<P -0) is given by [23] #= v / 3^2-^+^tan^ = 0…”
Section: Constitutive Behaviour Of Cohesive-frictional Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further loading leads to the localization of the deformation within the shear band (or in an array of parallel bands) without any strain hardening. There is a wide body of experimental evidence showing that the yield criterion for shear band formation in metallic [13][14][15][16] and ceramic glasses [17,18] as well as in polymers [19][20][21][22] depends on the hydrostatic stress and that the yield surface of these materials is adequately represented by either the Mohr-Coulomb or the Drucker-Prager yield criterion. Mathematically, the yield surface (<P -0) is given by [23] #= v / 3^2-^+^tan^ = 0…”
Section: Constitutive Behaviour Of Cohesive-frictional Materialsmentioning
confidence: 99%
“…They are measured by different methods, including the orientation of the shear bands during uniaxial compression, multiaxial tests in a confining sleeve, or the ratio between tensile and compressive strength. Keryvin et al [15], Lewandowski and Lowhaphandu [44] and Yuan et al [45] suggested that Zr-based glass shows limited pressure sensitivity with f$ < 10°. Others authors [16,46] maintain that these materials present a moderate pressure dependence with f> « 20°.…”
Section: Metallic Glasses Showed Wjw T And03\mentioning
confidence: 99%
“…For pressure-sensitive materials that obey Mohr-Coulomb yield criterion, the intersection angles are smaller, i.e., a < 90 and depend on the cone apex angle. 22 The conical indentations on the AC and SR specimens were performed using a diamond cone tip (cone angle 120 , tip radius 0.2 mm) that is normally used for Rockwell hardness measurements with an applied load of 980 N. Smaller indents were performed on the crosssection of the peened layer of the SP specimen using the MTS NanoXP indenter with a conical tip (cone angle 84. 6 , tip radius 1 mm) and a maximum load of 100 mN.…”
Section: A Pressure Sensitivitymentioning
confidence: 99%
“…The emphasis of this paper is on the temperature dependence of pressure sensitivity in BMGs. For this purpose, we employ indentation, which has been successfully employed to investigate the deformation mechanisms and pressure sensitivity in these materials [4,7,8,[12][13][14][15][16][17][18][19][20]. In addition to indentation, we studied the uniaxial compressive properties of BMGs as a function of temperature, as they are necessary to evaluate constraint factor and understand possible origins of its variation with temperature.…”
mentioning
confidence: 99%